KEPASTIAN HUKUM STATUS KEPEMILIKAN TANAH RUMAH SUSUN PERSPEKTIF HUKUM EKONOMI SYARIAH - Dzulkarnain Alghafuru Syahputra (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
The developer of the apartment is allowed to sell the apartment unit that has not been completed after fulfilling the requirements and obligations as regulated in Article 43 paragraph (2) of the Flats Law. This study aims to analyze and find the accuracy of using Article 378 of the Criminal Code to adjudicate violations of Article 43 paragraph (2) of the Flats Law related to the certainty of land ownership status as the basis for making PPJB and criminal responsibility for notaries against the occurrence of criminal acts in the deed he made related to with the principle of prudence of a notary in carrying out his office. The research method used in this study is normative juridical law research, the approach method used is the statutory regulation approach and the conceptual approach as well as the case approach. From the results of the research and discussion, it can be concluded first: the use of Article 378 of the Criminal Code which is applied to violations of Article 43 paragraph (2) of the Flats Law is inappropriate. The appropriate article for the violation is Article 110 of the Flats Law. Second: For criminal acts that are contained in a notary deed, it can cause the notary to be held criminally responsible for participating in helping the occurrence of a crime. In Sharia Economic Law, land ownership in flats includes haq al-jiwar which is included in the realm of al-irtifaq rights, where every occupant of the flat is entitled to the land where the house they live in is built. Therefore, the use of land should be by mutual agreement of all occupants or owners of the flat. If there is a violation of shared land use, sharia economic law does not clearly state the sanctions, but according to the author, sanctions in such land use violations are more related to tahzir punishments (orders) only, and do not reach the realm of Islamic criminality (hudud).Keywords: flats, violation, criminal, Haq al-Irtifaq.Â